Let's go through each calculation step-by-step to find the value of each expression.
1. Evaluate [tex]\( p + 5 \)[/tex] when [tex]\( p = -3 \)[/tex]:
[tex]\[
p + 5 = -3 + 5 = 2
\][/tex]
2. Evaluate [tex]\( q - 6 \)[/tex] when [tex]\( q = 4 \)[/tex]:
[tex]\[
q - 6 = 4 - 6 = -2
\][/tex]
3. Evaluate [tex]\( 6h \)[/tex] when [tex]\( h = -3 \)[/tex]:
[tex]\[
6h = 6 \times (-3) = -18
\][/tex]
4. Evaluate [tex]\( \frac{j}{4} \)[/tex] when [tex]\( j = -20 \)[/tex]:
[tex]\[
\frac{j}{4} = \frac{-20}{4} = -5
\][/tex]
5. Evaluate [tex]\( a + b \)[/tex] when [tex]\( a = 6 \)[/tex] and [tex]\( b = -3 \)[/tex]:
[tex]\[
a + b = 6 + (-3) = 3
\][/tex]
6. Evaluate [tex]\( c - d \)[/tex] when [tex]\( c = 25 \)[/tex] and [tex]\( d = 32 \)[/tex]:
[tex]\[
c - d = 25 - 32 = -7
\][/tex]
Putting all the results together:
[tex]\[
\begin{array}{l}
p + 5 = -3 + 5 = 2 \\
q - 6 = 4 - 6 = -2 \\
6h = 6 \times (-3) = -18 \\
\frac{j}{4} = \frac{-20}{4} = -5 \\
a + b = 6 + (-3) = 3 \\
c - d = 25 - 32 = -7 \\
\end{array}
\][/tex]
So the values of each expression are [tex]\(2\)[/tex], [tex]\(-2\)[/tex], [tex]\(-18\)[/tex], [tex]\(-5\)[/tex], [tex]\(3\)[/tex], and [tex]\(-7\)[/tex] respectively.